ACTN3 R577X polymorphism related to sarcopenia and physical fitness in active older women. (2nd January 2021) - Romero-Blanco, C.; Artiga González, M. J.; Gómez-Cabello, A.; Vila-Maldonado, S.; Casajús, J. A.; Ara, I.; Aznar, S.
Abstract: Background: As the population is getting older, physical activity promotion becomes a good strategy to increase quality of life in the elderly; but genetic condition also plays an important role. The purpose of this study was to examine the association of the ACTN3 R577X polymorphism with physical fitness and muscle mass in physically active older women. Methods: A cross-sectional study was performed with two groups of older women who practiced physical exercise regularly. The first cohort comprised 164 women (age 69.7 ± 3.2 years) and the second cohort 131 women (age 78.5 ± 3.0 years). The main outcome measures were anthropometric measures with assessment of sarcopenia and sarcopenic obesity, self-reported physical activity EXERNET questionnaire (EEPAQ), evaluation of physical fitness (muscle strength and flexibility test), and ACTN3 genotyping. Results: Women above 75 years old with allele R presented a higher risk of experiencing sarcopenia compared to ACTNR XX homozygous women (odds ratio 0.356, 95% confidence interval 0.139–0.915, p  = 0.026). Furthermore, statistically significant differences were found in the chair stand test ( p  = 0.04), as well as in the sit and reach test ( p  = 0.01), with better results for women below 75 years old with the ACTN3 XX genotype. Conclusions: Sarcopenia and physical fitness show differences based on the ACTN3 R577X genotype in active older women.